1995
DOI: 10.1002/bit.260480609
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic biodegradation of BTEX by two Thermus Species

Abstract: Two thermophilic bacteria, Thermus aquaticus ATCC 25104 and Thermus species ATCC 27978, were investigated for their abilities to degrade BTEX (benzene, toluene, ethylbenzene, and xylenes). Thermus aquaticus and the Thermus sp. were grown in a nominal medium at 70 degrees C and 60 degrees C, respectively, and resting cell suspensions were used to study BTEX biodegradation at the same corresponding temperatures. The degradation of BTEX by these cell suspensions was measured in sealed serum bottles against contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…To be able to rationally engineer such properties into mesophilic enzymes, a study of the determinants of the stability is an important task for basic and applied research. Although thermophiles degrading aromatic compounds such as BTEX (benzene, toluene, ethylbenzene, xylene isomers) and phenol/cresol have been isolated (19,20,21), the aromatic pathways in these organisms are not well studied, and there have been few reports on the characterization of the genes/proteins involved (22,23).…”
mentioning
confidence: 99%
“…To be able to rationally engineer such properties into mesophilic enzymes, a study of the determinants of the stability is an important task for basic and applied research. Although thermophiles degrading aromatic compounds such as BTEX (benzene, toluene, ethylbenzene, xylene isomers) and phenol/cresol have been isolated (19,20,21), the aromatic pathways in these organisms are not well studied, and there have been few reports on the characterization of the genes/proteins involved (22,23).…”
mentioning
confidence: 99%
“…Furthermore, degradation was greater at 25 °C than at 37 °C, but pH variations between 4.5 and 7 had little effect on the extent of the degradation. Chen and Taylor (1995) reported that two thermophilic bacterial strains, Thermus aquaticus and an unidentified Thermus sp. degraded ethylbenzene (in a mixture with other BTEX chemicals) by 18% after 45 days of incubation at 70 °C and by 32% after 45 days of incubation at 60 °C, respectively.…”
Section: Sediment and Soilmentioning
confidence: 99%
“…The partitioning and transport processes in water, soil, and aquatic life are also well characterized (ASTER 1995;Dewulf et al 1996;Kawamura and Kaplan 1983;Ligocki et al 1985;Swann et al 1983). Transformation and degradation processes have also been well characterized in air (Atkinson and Carter 1984;Atkinson et al 1978;Grovenstein and Mosher 1970;Herron and Huie 1973;Hoshino et al 1978;O'Brien et al 1975;Ohta and Ohyama 1985;Ravishankara et al 1978;Yanagihara et al 1977), water (Acton and Barker 1992;Anid et al 1993;Bouwer and McCarty 1984;Burback and Perry 1993;Ehrhardt and Petrick 1984;Gschwend et al 1982;Hutchins 1991;Masten et al 1994;Wakeham et al 1983;Wilson et al 1986), and in soil and sediment (Bestetti and Galli 1984;Chen and Taylor 1995;Hutchins 1991;Hutchins et al 1991;Jamison et al 1970;Ramanand et al 1995;Van der Linden and Thijsse 1965;Yadav and Reddy 1993;Zappi et al 1996). No data need is identified at this time.…”
Section: Identification Of Data Needsmentioning
confidence: 99%
“…Biodegradation at 50 o C to 70 o C by several Bacillus strains in batch studies has been reported for methanol (AlAwadhi et al 1989;Dijkhuizen and Artman 1990;Arfman et al 1992;Arfman et al 1992). Biodegradation of BTEX compounds at 45 o C to 77 o C by a Thermus species in a batch reactor has been demonstrated (Chen and Taylor 1995;Chen and Taylor 1997).…”
Section: Biological Description Of Haps At High Temperaturementioning
confidence: 99%